Individual Compounds of Rhodoila quadrifida Rhizomes and Roots: Isolating and Establishing Structure - A. V. Lezina; A. K. Whaley; A. O. Whaley; I. I. Terninko (Разработка и регистрация лекарственных средств, 2022)
Introduction. Medicinal plant raw materials, containing a wide range of various biologically active compounds, are of considerable interest as a likely source of new, pharmacologically active biologically active substances. One of the promising plants is Rhodiola quadrifida (Pall.) Fisch. & C.A. Mey, since the raw materials contain phenolic compounds and their derivatives, which cause anti-inflammatory, antioxidant and anticarcinogenic effects. In addition, this plant has considerable popularity in folk medicine as a dietary supplement.Aim. Isolation of individual compounds from rhizomes and roots of Rhodiola quadrifida and subsequent determination of their structure by NMR and mass spectrometry for phytochemical profiling.Materials and methods. Rhizomes and roots of Rhodiola quadrifida, purchased in the pharmacy of St. Petersburg (place and time of procurement according to the information on the package – Altai (near Barnaul), in March 2019. The ethanol extract fractions (ethanol, hexane, butanol, and water) obtained during sequential liquid-liquid extraction were examined on a LC-20 Prominence instrument (Shimadzu, Japan) with an SPD-M20A diode array detector to determine the chromatographic profile. The most promising ethyl acetate fraction was purified by column chromatography on open glass columns with sorbents of different selectivity and preparative chromatography [Smartlina (Knauer, Germany)] with a spectrophotometric detector. The structure of the obtained individual compounds was determined by NMR (Bruker Avance III 400 MHz, Germany) and confirmed by low-resolution mass spectrometry [Flexar FX-15 (PerkinElmer, USA)].Results and discussion. During the study, 7 individual compounds were isolated from the rhizomes and roots of Rhodiola quadrifida, namely 3,4-dihydroxybenzoic acid, 4-hydroxybenzoic acid, caffeic acid, ethyl gallate, catechin, epicatechin and tyrosol. These compounds were isolated for the first time from the raw materials of Rhodiola quadrifida. They are the major compounds and can characterize the phytochemical profile of raw materials, as well as determine the direction of pharmacological activity.Conclusion. For the first time, Rhodiola quadrifida was isolated from raw materials and the structure of 7 majority compounds was proved by NMR spectroscopy and mass spectrometry, which can serve as a foundation for further study of this species of Rhodiola and targeted study of its pharmacological activity in vitro and in vivo, considering the individual phytochemical profile.